A review of the therapeutic and biological effects of edible and wild mushrooms. Issue 2 (20th December 2021) - Anusiya, G; Gowthama Prabu, U; Yamini, N V; Sivarajasekar, N; Rambabu, K; Bharath, G; Banat, Fawzi
ABSTRACT: Throughout history, mushrooms have occupied an inseparable part of the diet in many countries. Mushrooms are considered a rich source of phytonutrients such as polysaccharides, dietary fibers, and other micronutrients, in addition to various essential amino acids, which are building blocks of vital proteins. In general, mushrooms offer a wide range of health benefits with a large spectrum of pharmacological properties, including antidiabetic, antioxidative, antiviral, antibacterial, osteoprotective, nephroprotective, hepatoprotective, etc. Both wild edible and medicinal mushrooms possess strong therapeutic and biological activities, which are evident from their in vivo and in vitro assays. The multifunctional activities of the mushroom extracts and the targeted potential of each of the compounds in the extracts have a broad range of applications, especially in the healing and repair of various organs and cells in humans. Owing to the presence of the aforementioned properties and rich phytocomposition, mushrooms are being used in the production of nutraceuticals and pharmaceuticals. This review aims to provide a clear insight on the commercially cultivated, wild edible, and medicinal mushrooms with comprehensive information on their phytochemical constituents and properties as part of food and medicine for futuristic exploitation. Future outlook and prospective challenges associated with the cultivation and processing of these medicinal mushrooms as functional foods are also discussed.